Multi-Omics Analysis of the Effect of cAMP on Actinorhodin Production in Streptomyces coelicolor - Nitta, Katsuaki; Carratore, Francesco Del; Breitling, Rainer; Takano, Eriko; Putri, Sastia P.; Fukusaki, Eiichiro (Frontiers in Bioengineering and Biotechnology, 2020)
CCyclic adenosine monophosphate (cAMP) has been known to play an important role in regulating morphological development and antibiotics production in Streptomyces coelicolor. However, the functional connection between cAMP levels and antibiotics production and the mechanism by which cAMP regulates antibiotics production remain unclear. In this study, metabolomics- and transcriptomics-based multi-omics analysis was applied to S. coelicolor strains that either produce the secondary metabolite actinorhodin (Act) or lack most secondary metabolite biosynthesis pathways including Act. Comparative multi-omics analysis of the two strains revealed that intracellular and extracellular cAMP abundance was strongly correlated with actinorhodin production. Notably, supplementation of cAMP improved cell growth and antibiotics production. Further multi-omics analysis of cAMP-supplemented S. coelicolor cultures showed an increase of guanine and the expression level of purine metabolism genes. Based on this phenomenon, supplementation with 7-methyl guanine, a competitive inhibitor of reactions utilizing guanine, with or without additional cAMP supplementation, was performed. This experiment revealed that the reaction(s) inhibited by 7-methyl guanine are mediating the positive effect on growth and antibiotic production, which may occur downstream of cAMP supplementation.